ANALISA DAN PERANCANGAN SISTEM INFORMASI PELAYANAN STOK BARANG GUDANG AKSESORIS SEPATU PADA PT.NIKOMAS GEMILANG - Ahmad Rufai; Budi Pangestu (Amal Insani Foundation, 2022)
This research aims to analyze and design an information system for the Shoe Accessories Warehouse Stock Service at PT Nikomas Gemilang, which has been running manually so that it is less than optimal, becoming a computerized system that is more accurate and relevant according to needs. The methodology used in this research is the SDLC (System Development Life Cycle) method. This method analyzes performance, information, application security, efficiency and service. The results achieved from the analysis and design of the Shoe Accessories Warehouse Stock Service information system at PT Nikomas Gemilang are that the service system has been computerized so that it can improve service and determine the Stock of Goods in the Warehouse smoothly and precisely in data information. The conclusion that we give is that this computerized system design makes it easier for companies, especially the Shoe Accessories Warehouse Stock Service Department in Service, to calculate the number of Stock Items available with accurate data information.